Cardiac myxoma as a rare acute heart failure etiology in paediatrics: A case report - Irien Eko Hermawati; Hanang Anugrawan Achmad; Pandit Bagus Tri Saputra; Rafelito Kharisma Rahardjo; Sofie Wardhani; Heroe Soebroto (Journal of the Pakistan Medical Association, 2024)
Cardiac myxoma is extremely rare in children. However, if not treated immediately, it may cause varying symptoms until sudden death. A-9-years old male Javanese child was brought to the emergency department of Prof. Soekandar General Hospital, Mojokerto with progressive dyspnoea since one month which got worse in the left decubitus position. There was no significant past medical history. Physical examination revealed hypotension, mitral stenosis, tricuspid regurgitation, and pulmonary congestion. Transthoracic echocardiography revealed a round pedunculated 3x3.3 cm mass in the Left Atrium that swingingly moved to the Left Ventricle during diastole. This was diagnosed provisionally as Myxoma with a differential of thrombus. After stabilization, he was referred to a tertiary hospital for emergency excision. Histopathology confirmed the myxoma. There were no symptoms and activity limitations during the 6 months follow-up. To the best of our knowledge, this is the first paediatric cardiac myxoma with Acute Heart Failure symptoms reported in Indonesia. Echocardiography is imperative for diagnosing myxoma. Appropriate and timely management results in an excellent outcome. Keywords: Tricuspid Valve, Diastole, Myxoma, Heart Neoplasms, Mitral Valve Stenosis, Dyspnea, Thrombosis, Hypotension